2022
DOI: 10.1021/acs.jmedchem.2c01300
|View full text |Cite
|
Sign up to set email alerts
|

Development of SOS1 Inhibitor-Based Degraders to Target KRAS-Mutant Colorectal Cancer

Abstract: Direct blockade of KRAS driver mutations in colorectal cancer (CRC) has been challenging. Targeting SOS1, a guanine nucleotide exchange factor, has arisen as an attractive approach for KRAS-mutant CRC. Here, we describe the development of novel SOS1 degraders and their activity in patient-derived CRC organoids (PDO). The design of these degraders as proteolysis-targeting chimera was based on the crystal structures of cereblon and SOS1. The synthesis used the 6-and 7-OH groups of a quinazoline core as anchor po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…While we were preparing this manuscript, Bian et al. disclosed their inhibitor-based SOS1 PROTAC 6 by recruiting the E3 ligase CRBN …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we were preparing this manuscript, Bian et al. disclosed their inhibitor-based SOS1 PROTAC 6 by recruiting the E3 ligase CRBN …”
Section: Introductionmentioning
confidence: 99%
“…While we were preparing this manuscript, Bian et al disclosed their inhibitorbased SOS1 PROTAC 6 by recruiting the E3 ligase CRBN. 22 Herein, we report the design and characterization of our inhibitor-based SOS1 PROTACs which hijack the other most commonly recruited E3 ligase VHL. Systematic structural modification of the linker length and composition offers us a potent, fast, cooperative, and selective SOS1 degrader ZZ151 (8c).…”
Section: ■ Introductionmentioning
confidence: 99%
“…PPI docking analysis of BI-68BS -bound SOS1 and lenalidomide-bound cereblon. Adapted in part with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Small Molecules Targeting Sos1mentioning
confidence: 99%
“…Among these, compound 49 with eight methylene units exhibited the most potent SOS1 17). 103 The search for the optimal length and conformation of linkers was rationally guided by the protein−protein docking of BI-68BS-bound SOS1 and lenalidomide-bound cereblon. This revealed that relatively short linkers were desirable, leading to the synthesis of 15 compounds.…”
Section: Sos1 Inhibitorsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] TPD has entered its third decade with both opportunities and challenges. [19][20][21][22][23][24][25][26][27][28] TPD techniques rely on the ubiquitin-proteasome system (UPS), which couples ubiquitylation, catalyzed by E1 activating enzyme, E2 conjugate enzyme and E3 ligase, and proteasome for degradation of target substrates. [29][30][31][32][33][34][35][36][37][38][39][40][41] The concept of PROTAC was first proposed in 2001, and the PROTAC technology has developed rapidly in the past 20 years.…”
Section: Introductionmentioning
confidence: 99%